Pemilihan Kepala Daerah Secara Langsung Dan Tidak Langsung Dalam Pandangan Fiqh Siyasah - Andina Resty Eliza; Adinda Frizi Ananta, Adinda; Haeqkal Rachman, Haeqkal; Mhd. Aufar Fajar, Aufar; Nurenzy Turahmi, Nurenzy (Tabayyun : Journal Of Islamic Studies, 2023)
Regional head elections have become the focus of ongoing debate in Indonesia. The two known electoral systems are the indirect system during the early days of independence and the direct system after the reform era. By considering the principles of siyasah jurisprudence such as justice, benefit, and popular sovereignty, we will explore the arguments for and against each system. It is hoped that this article can provide a better understanding of regional head election systems in the context of Islamic law and Indonesian society, as well as help optimize the system to achieve justice and benefit in a society based on Islam.